An Algebraic Method to Find the Symmedian Point of a Triangle. Issue 3 (1st June 2016) - Bani-Yaghoub, M.; Rhee, Noah H.; Sadek, Jawad
Summary: A relationship between the symmedian point of a triangle and the least-squares solution of a linear system is presented. The coordinates of the symmedian point are explicitly calculated as a solution to the linear system.